RUSSIA AND JAPAN WAR BASED ON MILITARY PERSPECTIVE - Syaiful Hidayat; Suyono Thamrin; Rudy Laksmono Widayatno (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2022)
War is an important thing that is necessary for each country to defend the territory, as it can be a deterrent factor against the opposing war effort. In the modern era, war is no longer made by the truce, but it has been more referring to technology, politics, economy, etc. In this study, we analyze the causes of the Russia-Japan War, the strategies used in the Russia-Japan War, and lessons learned in the Russia-Japan war based on a military perspective. The theories used are a threat, energy, and war strategy. The methodology used is the qualitative descriptive method. Data for this study came from document review. The data were analyzed based on the analysis promoted by Miles and Huberman. This study found that The cause of the Japan-Russia war is the war developed from Russia's and Japan's rivalry for dominance in Korea and Manchuria. Japan planned a strategy that could cut the relationship between Port Arthur and the outside world. One interesting Russian strategy in the Japan-Russia war is when a public outcry against Alekseyev as commander in chief compelled Nicholas to send Kuropatkin to take over the command, although Alekseyev remained as viceroy. The Russia-Japan war underlines that a successful limited war strategy mandates the following: developing military capability commensurate to the strategy and identification of decisive points in the campaign; fostering synergy between the military and the political leadership; shaping the diplomatic environment for favorable war termination and compelling communication of the limited nature of the war to both domestic and international audiences